2017
DOI: 10.1371/journal.pone.0182757
|View full text |Cite
|
Sign up to set email alerts
|

Oyster toadfish (Opsanus tau) boatwhistle call detection and patterns within a large-scale oyster restoration site

Abstract: During May 2015, passive acoustic recorders were deployed at eight subtidal oyster reefs within Harris Creek Oyster Sanctuary in Chesapeake Bay, Maryland USA. These sites were selected to represent both restored and unrestored habitats having a range of oyster densities. Throughout the survey, the soundscape within Harris Creek was dominated by the boatwhistle calls of the oyster toadfish, Opsanus tau. A novel, multi-kernel spectral correlation approach was developed to automatically detect these boatwhistle c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 23 publications
3
26
2
Order By: Relevance
“…No such correlations to temperature are described at other locations. Instead, Monczak, Berry, Kehrer, and Montie ()and Ricci, Bohnenstiehl, Eggleston, Kellogg, and Lyon () mention seasonal, lunar and daily calling rhythms as well as differences between recording locations (Montie et al., ) (Table ). Amorim, Vasconcellos, Marques, and Almada () observe seasonal patterns of emission of different sound types (croaks, grunt trains, boatwhistles) in Lusitanian toadfish ( Halobatrachus didactylus , Batrachoididae); these patterns are significantly correlated to the temperature in the Tagus estuary, Portugal.…”
Section: Calling Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…No such correlations to temperature are described at other locations. Instead, Monczak, Berry, Kehrer, and Montie ()and Ricci, Bohnenstiehl, Eggleston, Kellogg, and Lyon () mention seasonal, lunar and daily calling rhythms as well as differences between recording locations (Montie et al., ) (Table ). Amorim, Vasconcellos, Marques, and Almada () observe seasonal patterns of emission of different sound types (croaks, grunt trains, boatwhistles) in Lusitanian toadfish ( Halobatrachus didactylus , Batrachoididae); these patterns are significantly correlated to the temperature in the Tagus estuary, Portugal.…”
Section: Calling Activitymentioning
confidence: 99%
“…While many studies revealed a relationship between calling activity/sound characteristics and temperature, several studies failed to report such a relationship (cod—Brawn, ; oyster toadfish—Monczak et al., ; Ricci et al., ; Lusitanian toadfish—Amorim et al., ). A drop in the calling activity of the Lusitanian toadfish in late July despite high temperatures (Figure b) most likely reflects seasonal androgen changes according to the authors (the effects of sex steroids on fish acoustic communication are reviewed in Maruska & Sisneros, ).…”
Section: Sound Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at least three hydrophone are needed to pinpoint exact source location because multiple TOAD bearings can be calculated and intersected (Watkins and Schevill, 1972;Spiesberger and Fristrup, 1990;Møhl et al, 2001;Wahlberg et al, 2001). Hydrophone arrays potentially can determine fish distributions that could not be obtained with single hydrophone recordings, but require a higher level of sophistication for setting up, operating and analyzing the data (Ricci et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, fixed and towed hydrophones are now a popular tool for localizing the spatial and temporal nature of spawning populations of fishes that actively produce advertisement calls to attract mates (Rice and Bass, 2009;Locascio and Mann, 2011). This type of non-invasive monitoring provides long term, continuous information on animal behavior and abundance, and calling measurements in settings that are otherwise difficult to sample (Ricci et al, 2017).…”
Section: Introductionmentioning
confidence: 99%